When Artificial Intelligence Meets Printing The Evidence of Black Generation - Tongkai, Xu; Manjiang, Li; Shanmin, Li; Jiliang, Xie; Zhende, Yuan (EAI Endorsed Transactions on Scalable Information Systems, 2021)
Recent years wit a rapid development of new technologies. As a significant part, artificial intelligence leads to a great change of our life. While the color printing technique which is struggled with obstacles such as color reproducing now finds a revolutionary approach to overcome the difficulties. The new method significantly improved the accuracy although it requires the parallel computing process to deal with the complexity of computing. This paper firstly introduces the brief histories and the basics of black generation technique of the printing process and artificial intelligence. Then comes to the traditional techniques of black generation. In the next part we suggest an artificial intelligence approach to black generation. At last we make a comparison between various methods and point out the advantages of the new approach.
Keywords: Artificial Intelligence; Printing; Parallel Processing; Black Generation